2017
DOI: 10.1038/srep44351
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-like 4 Mediates Colonic Inflammation by Regulating Chemokine Transcript Stability via Tristetraprolin

Abstract: Many gastrointestinal diseases exhibit a protracted and aggravated inflammatory response that can lead to hypercytokinaemia, culminating in extensive tissue damage. Recently, angiopoietin-like 4 (ANGPTL4) has been implicated in many inflammation-associated diseases. However, how ANGPTL4 regulates colonic inflammation remains unclear. Herein, we show that ANGPTL4 deficiency in mice (ANGPTL4−/−) exacerbated colonic inflammation induced by dextran sulfate sodium (DSS) or stearic acid. Microbiota was similar betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 57 publications
3
19
0
Order By: Relevance
“…is also involved in the regulation of immune homeostasis, modulating inflammatory T-cells response and cytokines expression such as IL10 and IL1. These compelling evidences corroborated our in-silico data (Figure 4b) being also reported as immune activation repressor [49]. Remarkably, our experimental evidences parallel previous report about ANGPLT4, as an up-stream regulator of WNTpathway and an agonist of PKC, the main XAV-939 target [50].…”
Section: Discussionsupporting
confidence: 92%
“…is also involved in the regulation of immune homeostasis, modulating inflammatory T-cells response and cytokines expression such as IL10 and IL1. These compelling evidences corroborated our in-silico data (Figure 4b) being also reported as immune activation repressor [49]. Remarkably, our experimental evidences parallel previous report about ANGPLT4, as an up-stream regulator of WNTpathway and an agonist of PKC, the main XAV-939 target [50].…”
Section: Discussionsupporting
confidence: 92%
“…A study showed that nANGPTL4 is an orphan ligand that mainly controls lipid metabolism and cANGPTL4 binds-e.g., β-integrins, VE-cadherin, and claudin-5-to induce vascular leakage and tumor progression [19]. An increasing number of studies have indicated the possible involvement of ANGPTL4 in the development of cardiovascular diseases [20][21][22], inflammatory diseases [23][24][25][26], cancers [27][28][29], etc. However, there are still no reports on the role of ANGPTL4 in bacterial meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…Angptl4 protected against acute colonic in ammation and that its absence worsened the severity of in ammation [32]. As the critical enzyme in FA metabolism, SCD is responsible for the conversion of saturated FAs to unsaturated FAs, and oleic acid is one of the major products [33]. Researchers found that gut-speci c SCD-1 activity is necessary to control intestinal epithelial in ammation and synthetize oleate, and that dietary oleic acid provides protection against intestinal in ammation in vivo [34].…”
Section: Fp Intervention Promoted Lipid Metabolism Of the Colonic Epimentioning
confidence: 99%